S32 Associations between asthma severity, initial management and specialist review on length of stay and mortality outcomes. (12th November 2019) - Adamson, A; Robinson, S; Roberts, CM; Quint, JK; Calvert, J
Abstract : Introduction: Early treatment of asthma attack is recommended and improves outcomes. Using audit data of acute asthma admissions in secondary care, we investigated whether: Patients admitted with severe and life-threatening asthma were more likely to receive systemic steroids, beta-agonists, and a peak expiratory flow (PEF) measurement, and receive these more quickly, than patients with less severe asthma Patients with more severe asthma were more likely to be reviewed by a specialist Initial actions impacted on length of stay (LOS) and mortality Methods: The Royal College of Physicians National Asthma and COPD Audit Programme began a continuous audit on acute asthma in secondary care in November 2018. 170 hospitals in Britain provided data on asthma admissions from November 2018-March 2019. Data were collected on patient characteristics and care received. Multi-level logistic and linear regression were used to analyse associations between asthma severity (defined using NICE guidelines), care, and outcomes. Results: 10, 428 asthma admissions were inputted, of which 10, 242(98.2%) were suitable for analysis. 34.6% (N=3, 547), 51.4% (N=5, 266), and 14.0% (N=1, 429) of patients were admitted with moderate, severe, and life-threatening asthma respectively. 87.7% (N=8, 986) received systemic steroids on arrival, 91.3% (N=9346) were administered beta-agonists and 72.6% (N=7, 436) had their PEF measured on arrival. 76.8% (N=7, 870) of patients received a specialist respiratory review. After adjusting for age and hospital, patients with severe and life-threatening asthma were more likely to receive systemic steroids, beta agonists, and PEF measurement compared to those with moderate asthma (p<0.001), and were more likely to receive this sooner (p<0.001). Patients with more severe asthma were more likely to receive a specialist respiratory review (p<0.001). After adjusting for age and asthma severity, PEF measurement on arrival was associated with reduced mortality (adj-OR=0.27, 95%CI 0.08–0.75). Receipt of systemic steroids, beta-agonists, and PEF measurement within 1 hour of arrival was associated with a -3.6% (95%CI -7.7%-+0.5%), +1.9% (-2.1%-+6.0%) and -19.2% (-23.5%- -14.7%) change in LOS respectively. Conclusion: Patients with more severe asthma were more likely to receive optimal asthma care. PEF measurement on arrival was associated with survival and patients that received PEF within one hour had a shorter LOS.